The Analysis of Song Putri Reservoir Storage Area on Sedimentation Rate Using Mathematical Model Approach - Novi Andhi Setyo Purwono; Atiyah Barkah; Elvina Kusumawati; Rena Ning Tyas (Universitas Negeri Gorontalo, 2022)
Song Putri Reservoir is an artificial reservoir with the aim of irrigation channels for rice fields and flood control. This reservoir is located in Eromoko District, Wonogiri Regency Sedimentation modeling in the Song Putri reservoir is needed to analyze the amount of sediment deposition against the Song Putri Reservoir. To analyze the flow patterns and sediment distribution that occurs in reservoirs, SMS (Surface-water Modeling System) 8.0 Softwarse is used. This study aims to determine the flow patterns and effects of sediment distribution on reservoir changes. The data used include Song Putri Reservoir technical data, daily rainfall data for 10 years (2009-2018), sediment data, reservoir inflow data, and bathymetry maps. To analyze the magnitude of inflow and outflow of Song Putri Reservoir, hydrological analysis using empirical methods is used, while sedimentation modeling simulation uses SMS 8.0. Software based on the simulation, result the highest flow velocity in the 50 year return period is 0.097 m / s and the smallest is 0.00 m / s. Based on the simulation results of changes in the reservoirs base for 720 hours (1 month), the values ​​that in the return period of 50 years, 100 years and the highest 1000 years the highest was 5.795 m and the smallest of 0.001 m. Based on the calculation of prediction of sediment growth rates, it obtained the results of sediment growth rates with a percentage for a 50 year return period of 35.68% with a range of percentages between 19% - 21% and a percentage of 29.103% for a 100 year return period with a range of percentages between 22% - 24%, while the percentage growth rate of 1000 year return period sediments is 98 , 20% with a percentage range between 55% - 57%.